2015
DOI: 10.1103/physreva.91.032324
|View full text |Cite
|
Sign up to set email alerts
|

Universal photonic quantum gates assisted by ancilla diamond nitrogen-vacancy centers coupled to resonators

Abstract: We propose two compact, economic, and scalable schemes for implementing optical controlled-phase-flip and controlled-controlled-phase-flip gates by using the input-output process of a single-sided cavity strongly coupled to a single nitrogen-vacancy-center defect in diamond. Additional photonic qubits, necessary for procedures based on the parity-check measurement or controlled-path and merging gates, are not employed in our schemes. In the controlled-path gate, the paths of the target photon are conditionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…Similarly to a recent work on implementing the Magic Square Game with quantum dots [69], the ancillary system herein is used just like a catalyzer, left in the initial state after the operation and can be used again. Note that in any task based on distant spin or atomic qubits and traveling ancillary photons such as those in [54,55,58,[60][61][62][63][64]69], operations on three or more qubits are implicitly realized. Hence, considering a three-qubit operation as the basic building block enables a more systematic approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to a recent work on implementing the Magic Square Game with quantum dots [69], the ancillary system herein is used just like a catalyzer, left in the initial state after the operation and can be used again. Note that in any task based on distant spin or atomic qubits and traveling ancillary photons such as those in [54,55,58,[60][61][62][63][64]69], operations on three or more qubits are implicitly realized. Hence, considering a three-qubit operation as the basic building block enables a more systematic approach.…”
Section: Discussionmentioning
confidence: 99%
“…In the common scenario [54,55,58,[60][61][62][63][64], a threequbit operation can be considered for an ancillary photon and two spatially separated spin qubits to be entangled. We will introduce such a three-qubit operation as the basic building block, show how it can be realized and used for preparing arbitrary size W states of spins qubits.…”
Section: A Three-qubit Operation For Deterministic Preparation Of W S...mentioning
confidence: 99%
“…A measurement-based optical CNOT gate was demonstrated [27] in 2007. Moreover, parallel and hyperparallel deterministic optical CNOT gates prepared from photonmatter emitters have been proposed in recent years [28][29][30][31] and cross-Kerr approaches [32]. Fig.…”
Section: Photonic Architecture Of the Fredkin Gatementioning
confidence: 99%
“…The emitted photon-matter entangling platform is at the heart of the photon-based or matterbased scalable quantum computing [22,52], Bell-state analysis [60], entanglement detection [61], and it has been received great progress in experiment. In 2008, Fushman et al [62] observed phase shift π/4 in QD-cavity system.…”
Section: Compact Quantum Circuit For Implementing Hyper-parallel C 2 ...mentioning
confidence: 99%
“…In recent years, there have been a number of hallmark demonstrations of quantum entanglement between an emitted single photon and a stored NV centre electron spin (or between two separated NV centre spins) [48][49][50]. Based on NV-centre-emission-based entanglement, some interesting schemes for implementing universal gates on NV centre electronic [22] or photonic qubits [51,52], and hyperentanglement purification and concentration were also proposed recently [53].…”
Section: Introductionmentioning
confidence: 99%